The Impact of Tax knowledge in compliance costs: Applied Research (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research Sought to Determine the Relationship and  impact  between the tax knowledge in dimensions  of the tax compliance costs (monetary costs, time costs, psychic costs) Since the sample included 81 individuals represented by the Executive directors and Financial  and Accountant working in the Joint-stock company,  A questionnaire was used as a tool for data collection and its analysis.  For the purpose of analyzing the research data the statistical package for social science, SPSS. The most important tools used in the statistical analysis are:(standard deviation, and simple linear regression, percentages,  arithmetic mean, Cronbach's alpha, F-test, T- Test). The research found a weakness attention sample organizations research, Tax knowledge despite its impact on reducing the costs of compliance, and also research found a lack of the fact of tax services provided by tax administration,  the most of the organizations had hired services   consultants and experts for information and guidance to complete the tax measures, which have contributed to increasing compliance costs.